Organic Geochemistry - Organic Geochemistry (Elsevier, 2026)
Organic Geochemistry serves as the only dedicated medium for the publication of peer-reviewed research on all phases of geochemistry in which organic compounds play a major role. The Editors welcome contributions covering a wide spectrum of subjects in the geosciences broadly based on organic chemistry (including molecular and isotopic geochemistry), and involving geology, biogeochemistry, environmental geochemistry, chemical oceanography and hydrology.
FI 0.79
Q2
Keywords: Earth; Space & Environmental Sciences; Geochemistry & Mineralogy; Geoquímica; Mineralogía; Acuerdos transformativos; Transformative agreements; Compuestos orgánicos; Geociencias; Sedimentos; Suelos